Care plan for the patient with a dependent personality disorder - Ana María Ruiz Galán; Mª Carmen Pérez González; Susana Bravo Ferrón (Fundación para el Desarrollo de la Enfermería, 2010)
Personality is unique for each individual and can be defined as the dynamic collection of characteristics relative to emotions, thought and behaviour.Personality trout's only mean a Personality Disorder (PD) when they are inflexible and maladjusted and cause notable functional deterioration or uneasiness.According to Bermudez personality is "the enduring organization of structural and functional features, innate and acquired under the special conditions of each one's development that shape the particular and specific collection of behaviour to face different situations".According to the Diagnostic a Statistical Manual of Mental Disorders (DSM-IV), a Personality Disorder is "an enduring pattern of inner experience and behavior that deviates markedly from the expectations of the person's culture is pervasive and an inflexible, is stable over time and leads to distress or impairment. The onset of these patterns of behaviour is the beginning of the adulthood and, in rare instances, early adolescence".There are several types of Personality Disorders (paranoid, schizoid, borderline, antisocial, dependent...). Dependent Personality Disorder is one of the most frequent in the Mental Health Services.People who suffer from this disorder are unable to take a decision by themselves because they don't have confidence in themselves. They need a lot of social support and affection until the point of deny their individuality by subordinating their desires to other person's desires and permitting these persons to manage their lives. Maybe they feel desolated by separation and loss and can support any situation, even maltreatment to keep a relationship.As we a deduce this diagnosis is sensible to cultural influences. This work aims to elaborate an standarized plan of cares for the patient with Dependent Personality Disorder by using nursing Diagnosis of NANDA II, Outcomes Criteria (NOC) and Interventions Criteria (NIC).